Corporate governance in the US and global settings - Ferris, Stephen P.; John, Kose; Makhija, Anil K. (Emerald, 2014)
Volume 17 of Advances in financial economics, entitled "Corporate governance in the US and global settings" will provide further insights into corporate governance in the US & global economic and financial environment by publishing international, within-country and cross-country comparative studies. The volume will be edited by the series editors, Kose John, New York University, Anil Makhija, Ohio State University, and Stephen P. Ferris, University of Missouri.
Keywords: Corporate governance.; Corporations.; elektronické knihy; electronic books